PENGARUH KONTRAK PSIKOLOGIS DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASI GURU SMK NEGERI KABUPATEN LAMPUNG BARAT - Uza Sukmana (Jurnal Manajemen Pendidikan, 2016)
The objective of this research is to obtain information about the effect of psychological contract and job motivation on teacher organization commitmen. It was quantitative research with survey method in SMK Negeri Kabupaten Lampung Barat.The research was conducted to all teacher of SMK Negeri Kabupaten Lampung Barat by using a survey method with path analysis applied in testing hypothesis. The number 154 teachers as sample was selected by using Slovin formula.The research conlude: (1) There is a direct positive effect of psychological contract on organization commitmen. (2) There is a direct positive effect of job motivation on organization commitmen. (3) There is a direct positive of psychological contract on job motivation.